The Evolution of Palliative Care: A Social Paradigm - Discala, Paul (Journal of Student Research, 2024)
Indisputably, palliative care practices within the United States embellish modifications contingent upon societal apprehensions regarding death and the dying process. Further, these malleable societal attitudes are heavily influenced by geopolitical catalysts such as world health crises and periods of armed conflict that result in mass casualties. As a direct result, rapid advancements to comfort care practices are established for patients experiencing discomfort from chronic ailments that may impede upon an amicable dying process. As such, a thorough examination of previously published research will demonstrate these fluctuations to the generalized public attitudes of morbidity in conjunction with the progressive degrees of value and importance given to those who have departed. The resulting increase in compassion given to such individuals in the final stages of life consequently stimulates advancements made to future healthcare related practices and technologies. Ultimately, this research aims to explore the key historical catalysts that have altered the societal and cultural perceptions towards death and dying, in correlation to the quality and effectiveness of palliative medical care over time. The subsequent findings will contribute to the general existing body of knowledge regarding palliative care interventions, providing standardized insights into the historic evolutions and current challenges to the implementation of palliative care interventions within the United States.